¿A qué juega barbie? obligatoria y heterosexualidad agencia cultural - Garzón M, Maria Teresa (CALLE14: revista de investigación en el campo del arte, 2011)
Through the assessment of an experience in cultural agency, this article of reflection tackles the concept of mandatory heterosexuality, or heteronormativity, and sees it as a political system that has an impact on the life of women, because it constrains them in a dichotomic form of existing, relating and defining themselves. Cultural agency is proposed as a way of questioning that political system —with an impact on the symbolic and imaginary aspects that make it hegemonic— thus contributing to its disassembly.